Rapid and Visual Detection of Monkey B Virus Based on Recombinase Polymerase Amplification - Xinlan Chen; Chenchen Liu; Fangxu Li; Junhui Zhou; Zanheng Huang; Haili Zhang; Hualei Wang; Pei Huang; Zengguo Cao; Sandra Chiu (Zoonoses, 2023)
Monkey B virus (BV) infection in humans and other macaque species has a mortality rate of approximately 80%. Because BV infects humans through bites, scratches, and other injuries inflicted by macaques, the simple and rapid diagnosis of BV in field laboratories is of great importance to protect veterinarians, laboratory researchers, and support personnels from the threat of infection. Two recombinase polymerase amplification (RPA) assays with a closed vertical flow (VF) visualization strip (RPA-VF-UL27 and RPA-VF-US6) were developed that target two conserved genes combined with a one-off, closed visualization strip device. We compared the sensitivities and specificities of the two assays after optimization of the reaction conditions. The performance of RPA-VF-US6 at room temperature was determined to evaluate its potential in point-of-care (POC) testing. RPA-VF-US6 specifically detected the positive plasmid control (rather than nucleic acids of herpesviruses) with a detection limit of 28 copies, while RPA-VF-UL27 had cross-reactivity with HSV-1, but even 3.4 copies of plasmid standards were readout by this assay. Moreover, RPA-VF-US6 had excellent performance at room temperature (the detection limit was 2,800 plasmid copies), indicating the potential of RPA-VF-US6 in POC testing. We developed two RPA assays for BV visualization diagnosis. RPA-VF-US6 is a simple, rapid, and specific detection method for BV. The entire reaction can be performed at a constant temperature within 30 min, suggesting the potential of RPA-VF-US6 for POC testing in field laboratories without sophisticated instruments.